Prevalence and risk factors for diabetic neuropathy in an urban south Indian population: the Chennai Urban Rural Epidemiology Study (CURES-55) - Pradeepa, R.; Rema, M.; Vignesh, J.; Deepa, M.; Deepa, R.; Mohan, V. (Diabetic medicine, 2008)
Aims  This study was conducted to determine the prevalence of, and risk factors for, diabetic neuropathy (DN) in south Indian Type 2 diabetic subjects. Methods  Subjects were recruited from the Chennai Urban Rural Epidemiology Study, conducted on a representative cohort from Chennai city. A total of 1629 diabetic subjects were included, of whom 1291 were known to have diabetes (KD) subjects and 338 were randomly selected newly detected diabetic (NDD) subjects. Neuropathy was diagnosed if vibratory perception threshold at the great toe, measured by biothesiometry, exceeded mean + 2 sd of a healthy non‐diabetic study population aged 20–45 years (cut point ≥ 20 V). Results  The overall prevalence of DN was 26.1% (age‐adjusted 13.1%) with no significant difference in gender. The prevalence of neuropathy was significantly higher in KD subjects compared with NDD subjects (27.8 vs. 19.5%, P = 0.002). The prevalence of diabetic retinopathy (24.1 vs. 15.3%, P < 0.0001) and hypertension (51.1 vs. 40.0%, P < 0.0001) were higher in those with neuropathy compared with those without. The odds ratio for neuropathy in subjects with duration of diabetes > 15 years compared with ≤ 5 years was 5.7 (95% confidence interval: 3.52–9.08, P < 0.0001). Regression analysis showed age (P < 0.0001), glycated haemoglobin (P = 0.001) and duration of diabetes (P = 0.045) to be significantly associated with neuropathy. Conclusions  This cross‐sectional population‐based study shows that, among urban south Indian Type 2 diabetic subjects, the prevalence of DN is 26.1% and that DN is significantly associated with age, glycated haemoglobin and duration of diabetes.